Growth of Micro, Small and Medium Enterprises in Chittoor District, Andhra Pradesh - K. Munaswamy Reddy; P. Sankarappa and B. Bhagavan Reddy
Andhra Pradesh (AP) is known for its diversity in terms of geography, human and natural resources and composition of industry. Rayalaseema is a backward region in terms of per capita income, employment opportunities, pace of industrialization and so on. Chittoor district is one of the four districts of Rayalaseema region. In this paper, an attempt is made to evaluate the growth of MSMEs in terms of number of units, capital employed to procure plant and machinery, total capital invested in aggregate assets and employment generated from the period of enactment of MSMEs Development Act, 2006. The study revealed that there is a rapid and significant growth in small and micro enterprises in terms of number of units, investment and employment generation when compared to medium enterprises in the district. The trend in the growth is spectacular in the case of small enterprises relative to microenterprises. The revision/modification of definition in terms of investment limit in the MSME Act and positive initiatives of government such as subsidy, incentives, rebates, concessions, provision of raw materials etc, have brought in significant changes in the industrial outlook of Chittoor district in the recent past as compared to the period before 2006.